Host determinants of reinfection with schistosomes in humans: a systematic review and meta-analysis. - Evaristus Chibunna Mbanefo; Nguyen Tien Huy; Anita Akpeedje Wadagni; Christine Ifeoma Eneanya; Obioma Nwaorgu; Kenji Hirayama (Public Library of Science (PLoS), 2014)
Schistosomiasis is still a major public health burden in the tropics and subtropics. Although there is an effective chemotherapy (Praziquantel) for this disease, reinfection occurs rapidly after mass drug administration (MDA). Because the entire population do not get reinfected at the same rate, it is possible that host factors may play a dominant role in determining resistance or susceptibility to reinfection with schistosomes. Here, we systematically reviewed and meta-analyzed studies that reported associations between reinfection with the principal human-infecting species (S. mansoni, S. japonicum and S. haematobium) and host socio-demographic, epidemiological, immunological and genetic factors.PubMed, Scopus, Google Scholar, Cochrane Review Library and African Journals Online public databases were searched in October 2013 to retrieve studies assessing association of host factors with reinfection with schistosomes. Meta-analysis was performed to generate pooled odds ratios and standardized mean differences as overall effect estimates for dichotomous and continuous variables, respectively. Quality assessment of included studies, heterogeneity between studies and publication bias were also assessed. Out of the initial 2739 records, 109 studies were included in the analyses, of which only 32 studies with 37 data sets were eligible for quantitative data synthesis. Among several host factors identified, strong positive association was found with age and pre-treatment intensity, and only slightly for gender. These factors are major determinants of exposure and disease transmission. Significant positive association was found with anti-SWA IgG4 level, and a negative overall effect for association with IgE levels. This reconfirmed the concept that IgE/IgG4 balance is a major determinant of protective immunity against schistosomiasis. Other identified determinants were reported by a small number of studies to enable interpretation.Our data contribute to the understanding of host-parasite interaction as it affects reinfection, and is a potential tool to guide planning and tailoring of community interventions to target high-risk groups.